Answer:
it's yes
Step-by-step explanation:
Answer:
![(f-g)(x)= x^2-4x-5](https://tex.z-dn.net/?f=%28f-g%29%28x%29%3D%20x%5E2-4x-5)
Step-by-step explanation:
We have the two functions:
![f(x)=x^2-3x-10\text{ and } g(x)=x-5](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E2-3x-10%5Ctext%7B%20and%20%7D%20g%28x%29%3Dx-5)
And we want to find (f-g)(x).
(f-g)(x) is equivalent to f(x)-g(x).
Therefore:
![\begin{aligned} (f-g)(x)&=f(x)-g(x)\\ &=(x^2-3x-10)-(x-5)\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%20%28f-g%29%28x%29%26%3Df%28x%29-g%28x%29%5C%5C%20%26%3D%28x%5E2-3x-10%29-%28x-5%29%5Cend%7Baligned%7D)
Simplify:
![\begin{aligned} &=x^2-3x-10-x+5 \\ &=(x^2)+(-3x-x)+(-10+5) \\ &=x^2-4x-5\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%20%26%3Dx%5E2-3x-10-x%2B5%20%5C%5C%20%26%3D%28x%5E2%29%2B%28-3x-x%29%2B%28-10%2B5%29%20%5C%5C%20%26%3Dx%5E2-4x-5%5Cend%7Baligned%7D)
Therefore:
![(f-g)(x)= x^2-4x-5](https://tex.z-dn.net/?f=%28f-g%29%28x%29%3D%20x%5E2-4x-5)
Trigonometry would help with this question.
The area of a regular hexagon is ((3√3)s^2)/2 where s is the side.
Plugging in 2 gives us 6√3 or 10.39 feet.
-2(5y-20) - 5y = -5
-10y + 40 - 5y = -5
-15y + 40 = -5
-15y = -45, y = 3
x = 5(3) - 20
x = 15 - 20, x = -5
Solution: x = -5, y = 3... or (-5,3)
The answer to the question is A